2011
DOI: 10.15395/mkb.v43n4.70
|View full text |Cite
|
Sign up to set email alerts
|

Polimorfisme Gen MMP-9, Ekspresi MMP-9, dan Indeks Apoptosis Sel Serviks pada Kehamilan 21–36 Minggu

Abstract: Ekspresi berlebihan serta aktivasi beberapa matriks metaloproteinase (MMP) sebelum persalinan mengarah pada degradasi jaringan amnion korion yang secara klinis disebut ketuban pecah dini (KPD). Peningkatan aktivitas MMP akibat polimorfisme gen matrik metaloproteinase-9 (MMP-9) (C-1562T) akan diikuti oleh apoptosis. Penelitian ini bertujuan mencari perbedaan ekspresi MMP-9, indeks apoptosis (IA) sel serviks, serta polimorfisme gen MMP-9 (C-1562T) pada kehamilan 21-36 minggu tanpa dan disertai KPD. Penelitian in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…(15) Increased concentrations of interleukin-6 (IL-6), C-reactive protein (CRP), and matrix metalloproteinase 9 (MMP-9) in the fetal and neonatal compartments have been shown to be associated with increased risk of preterm delivery. (16) MMP-9 expression, apoptosis index (IA) of cervical cells, and MMP-9 gene polymorphism (C-1562T) in pregnancies of 21-36 weeks without and with PROM have been demonstrated by Sabarudin et al, (17) who found no significant differences in MMP-9 expression and cervical cell IA between preterm delivery with PROM and preterm delivery without PROM.…”
Section: Discussionmentioning
confidence: 92%
“…(15) Increased concentrations of interleukin-6 (IL-6), C-reactive protein (CRP), and matrix metalloproteinase 9 (MMP-9) in the fetal and neonatal compartments have been shown to be associated with increased risk of preterm delivery. (16) MMP-9 expression, apoptosis index (IA) of cervical cells, and MMP-9 gene polymorphism (C-1562T) in pregnancies of 21-36 weeks without and with PROM have been demonstrated by Sabarudin et al, (17) who found no significant differences in MMP-9 expression and cervical cell IA between preterm delivery with PROM and preterm delivery without PROM.…”
Section: Discussionmentioning
confidence: 92%